2017
DOI: 10.1371/journal.pone.0189617
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-35 mitigates the function of murine transplanted islet cells via regulation of Treg/Th17 ratio

Abstract: Pancreatic islet transplantation is a promising treatment for type 1 diabetes (T1D). Interleukin-35 (IL-35) is a recently discovered cytokine that exhibits potent immunosuppressive functions. However, the role of IL-35 in islet transplant rejection remains to be elucidated. In this study, we isolated islet cells of BALB/c mouse and purified CD4+ T cell subsets of a C57BL/6 mouse. The model for islet transplantation was established in vitro by co-culture of the islet cells and CD4+ T cells. IL-35 (20 ng/ml) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The signature cytokine IFN‐γ has been detected consistently in recipient sera, islet allografts, and in in vitro assays of T cell stimulation . More recently, however, emerging literature suggests a significant role of Th17 responses in allogeneic as well as in xenogeneic islet rejection . Drawing from our previous work using a pig‐to‐B6 mouse islet transplant model in which a predominant Th17 anti‐porcine immune response was identified during acute rejection, we examined if the human Th17 response contributed to xenogeneic porcine islet rejection in our HuMice.…”
Section: Discussionmentioning
confidence: 99%
“…The signature cytokine IFN‐γ has been detected consistently in recipient sera, islet allografts, and in in vitro assays of T cell stimulation . More recently, however, emerging literature suggests a significant role of Th17 responses in allogeneic as well as in xenogeneic islet rejection . Drawing from our previous work using a pig‐to‐B6 mouse islet transplant model in which a predominant Th17 anti‐porcine immune response was identified during acute rejection, we examined if the human Th17 response contributed to xenogeneic porcine islet rejection in our HuMice.…”
Section: Discussionmentioning
confidence: 99%
“…The most critical ability of IL‐35 its ability to induce the differentiation of CD4 + Foxp3 ‐ Tregs (iTr35), which can once again secrete IL‐35, thus ensuring that IL‐35 maintains a strong immunosuppressive ability and inhibits the effects of multiple effector T cells, such as Th1 and Th17 cells, in vitro and in vivo . More importantly, previous studies on IL‐35 mainly focus on autoimmune diseases, but recent studies show that IL‐35 can effectively alleviate allograft rejection; thus, IL‐35 may become a new potential target for the treatment of allograft rejection …”
Section: Discussionmentioning
confidence: 99%
“…40 More importantly, previous studies on IL-35 mainly focus on autoimmune diseases, but recent studies show that IL-35 can effectively alleviate allograft rejection; thus, IL-35 may become a new potential target for the treatment of allograft rejection. [9][10][11] Mesenchymal stem cells exhibit multidirectional differentiation potential as well as migration, paracrine, and immunosuppressive activities and have gradually become promising candidates for cell-based immunotherapy. Studies have shown that MSCs can induce the formation of Tregs and inhibit the proliferation of inflammatory Th1 and Th17 cells, 41 exerting significant therapeutic effects on various disease models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations